Comparison of age-dependent quantitative changes in the male labial gland secretion of Bombus terrestris and Bombus lucorum - Zácek, Petr; Kalinová, Blanka; Sobotník, Jan; Hovorka, Oldrich; Ptácek, Vladimír; Coppée, Audrey; Verheggen, François; Valterová, Irena (Journal of chemical ecology, 2009)
Age-related changes of antennal-active components of male labial gland extracts were studied in two closely related bumblebee species, Bombus terrestris and B. lucorum. In B. terrestris, compounds eliciting electroantennogram (EAG) responses of virgin queens were ethyl dodecanoate, 2,3-dihydrofarnesal, 2,3-dihydrofarnesol, hexadecan-1-ol, octadeca-9,12,15-trien-1-ol, and geranylcitronellol. Compounds that elicited EAG responses from queens of B. lucorum were ethyl dodecanoate, ethyl tetradec-7-enoate, ethyl tetradec-9-enoate, ethyl hexadec-9-enoate, hexadecan-1-ol, hexadec-7-enal, octadeca-9,12-dien-1-ol, octadeca-9,12,15-trien-1-ol, and octadecan-1-ol. Quantities of these compounds in the labial glands changed significantly over the lifetime of the respective males of the two species. In both species, concentrations of the respective compounds reached their maximum within seven days after eclosion. Subsequently, a rapid decrease in the amount of EAG-active compounds occurred in B. terrestris, whereas in B. lucorum the amount of active compounds stayed approximately constant or decreased at a slow rate. Microscopy showed that in B. terrestris secretory cells of the labial glands undergo apoptosis from the fifth to the tenth day of life, whilst in B. lucorum labial gland cells remain unchanged throughout the life of the males.
Keywords: sexuální lákadla; Animals; elektrofyziologie; Gas Chromatography-Mass Spectrometry; Microscopy, Electron, Transmission; včely; věkové faktory; transmisní elektronová mikroskopie; zvířata; mužské pohlaví; Bees; Male; Age Factors; plynová chromatografie s hmotnostně spektrometrickou detekcí; Electrophysiology; Sex Attractants; exokrinní žlázy; Exocrine Glands